PENGGUNAAN METODE FINGER PAINTING UNTUK MENINGKATKAN KREATIVITAS DAN MOTORIK HALUS ANAK PADA TK ABA SAKINAH DESA SUKA MAKMUR - Sri Rahayu Pohan Sri Rahayu Pohan; Nurlaili A Nurlaili A (STAI Nusantara Banda Aceh, 2005)
Childhood is a golden period in the cognitive, creative, and fine motor development of children. One method that can be used to stimulate these aspects is the finger painting method. This method allows children to express their creativity through direct contact with paint using their fingers. This study aims to analyze the effectiveness of the use of the finger painting method in improving children's creativity and fine motor skills at ABA Sakinah Kindergarten, Suka Makmur Village. This study uses a qualitative approach with a classroom action research (CAR) method. Data were obtained through observation, interviews, and documentation of 20 children aged 4-5 years. The results show that the finger painting method is able to improve children's creativity in freely creating various shapes and colors. In addition, this activity also contributes to the development of children's fine motor skills, such as finger coordination, grasping skills, and hand dexterity. Thus, the finger painting method can be used as an effective learning strategy to support early childhood development.